Quand l’État décrète le marché : le cas du Plan Borloo - Florence Gallois; Martino Nieddu (Revue de la Régulation)
This paper aims to discuss the real capacity of régulation of the institutional arrangement introduced by the French Plan Borloo, which aimed to create both a sector and a market. We construct a corpus in order to characterize the real régulation in lifestyle and home care services (especially the social relations engaged by services production and the firm behaviour face to these institutional arrangements). We show that the institutional arrangements of the Plan Borloo failed both to organize an autonomous and deterritorialized market, and to mark the border of a (dual) sector. Nevertheless, the institutional arrangement of the Plan are mobilised by the actors. Arrangements do system with extra-sectorial institutional arrangement in the core of the productive models of firms. De facto, the forms of the régulation that appears are territorialized and cannot be contained in the sectorial borders defined by the Plan Borloo.